2012
DOI: 10.1186/1297-9716-43-30
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of homologous and heterologous adaptive immune responses in porcine reproductive and respiratory syndrome virus infection

Abstract: The present study characterized the homologous and heterologous immune response in type-I porcine reproductive and respiratory syndrome virus (PRRSV) infection. Two experiments were conducted: in experiment 1, eight pigs were inoculated with PRRSV strain 3262 and 84 days post-inoculation (dpi) they were challenged with either strain 3262 or strain 3267 and followed for the next 14 days (98 dpi). In experiment 2, eight pigs were inoculated with strain 3267 and challenged at 84 dpi as above. Clinical course, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 32 publications
7
68
0
1
Order By: Relevance
“…Thus, despite we are assuming again the worst case scenario for V pigs, the impact of vaccination on the viral transmission is still evident. Regarding the challenge strain 3267, when used in previous experiments (Díaz et al, 2012) it was shown that most animals developed a viremia long enough to cover the entire exposure phase, being thus adequate for the purpose of the present study. The results of the infection with strain 3267 can be considered as typical of an average genotype 1 subtype 1 isolate when inoculated in young pigs (Martínez-Lobo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, despite we are assuming again the worst case scenario for V pigs, the impact of vaccination on the viral transmission is still evident. Regarding the challenge strain 3267, when used in previous experiments (Díaz et al, 2012) it was shown that most animals developed a viremia long enough to cover the entire exposure phase, being thus adequate for the purpose of the present study. The results of the infection with strain 3267 can be considered as typical of an average genotype 1 subtype 1 isolate when inoculated in young pigs (Martínez-Lobo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Group NV was left unvaccinated and remained as naïve controls. On the 35th day postvaccination (dpv), 14 NV pigs were separated, housed in an isolated room and inoculated intranasally with 2 ml (1 ml/ nostril) of a suspension containing 10 5.5 TCID 50 /ml of a genotype 1 PRRSV strain designated as 3267 Díaz et al, 2012;Gimeno et al, 2011). The inoculated animals were designated as ''seeder'' pigs (SP).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…PRRSV control has proven to be difficult, among other causes because immunity against one strain does not preclude protective immunity against a different one [17,18,19]. The ideal of a universally effective vaccine, namely, one that could protect against all existing PRRSV strains, is far from reach.…”
Section: Introductionmentioning
confidence: 99%